New names of fossil Rubus (Rosaceae). Addendum I - Doweld, Alexander B. (Phytotaxa, 2019)
The nomenclature of some fossil homonyms of Rubus is additionally resolved. Fossil Rubus mucronatus Palamarev, being an illegitimate later homonym of extant Rubus mucronatus Seringe, is re-named as Rubus eubaticus nom. nov. Rubus ellipticus Pavlyutkin (fossil) is replaced by a new name Rubus primoricus nom. nov., because of the earlier homonym, Rubus ellipticus Smith (extant).